Carte, autor şi model uman în Predosloviile vechi româneşti - Laura Lazăr Zăvăleanu (Revista de Istorie și Teorie Literară)
The prefaces of the Romanian ancient texts often feature the dialectic relation between the book and the writer – in the wide connotation of the term, including the editor of the text, the copyist, the translator, the type-setter and, of course, the original author of the ‘escort text’ – and configures, from various typologies, an ideal human model upon which the entire motivation of writing is being set up. Turned into an exemplary reference – “there is no other thing more precious, necessary and useful to all of us” (The Preface of Gregory, the Metropolitan of Wallachia to the Collection of Christian Questions and Answers, 1765), the book will thus reveal, together with the “useful knowledge brought to the community”, the idea of recovering the reader’s soul by means of “bringing him to light out of the obscurity of ignorance” (The Preface signed by Neofit, the Metropolitan of Hungarian Wallachia to the Celebration Homilies, 1742). In such a manner the book will lay out exemplary portraits which embody the main virtues so much appreciated in this period. From this perspective, we will analyze to what extent the author of the preface himself gathers the attributes of an ideal protagonist of this epoch, which are his deontological relations to writing and to the reader to whom he addresses and how – either we speak of self – referentiality of the “lover of labor”, while printing the text, of the invocation of the auctoritas or of the panegyric discourse, re-traceable in the encomiums to aulic or religious authorities – such prefaces remain always centred upon and feature a whole strategy of focusing on certain complex human prototypes (the saint, the hero, the good Christian, praying and merciful, the scholar – crusader, the zealous, the discerner, the enlightened king, the spiritual founder – prelate, etc.). On such premises it is our intention to recompose a panoramic image of the axiological system of a world in which the relationship with the divinity and the ‘neighbor near by’ are facing the challenge of a deep reconfiguration as a consequence to the direct access to the book written in their own language.